STRATEGY FOR SUSTAINABLE MARINE TOURISM DEVELOPMENT IN KONENG BEACH, DUMAI CITY, RIAU - Veronica, Dinny; Zulkarnain, Zulkarnain; Efizon, Deni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Koneng Beach is one of the beaches located in Teluk Makmur Village, Medang Kampai District, Dumai City, Riau Province, which has tourism potential. However, the potential of Koneng Beach has not been accompanied by the development of new tourism, facilities tourism, accessibility and attractions that support tourist appeal. The first stage in this study determines the potential resources owned by Koneng Beach with the concept of Sustainable Coastal Tourism (SCT) and 4A (Attraction, Accessibility, Amenity and Ancillary). Sustainable tourism development is based on eight aspects of tourism development. The priority strategy for developing Koneng Beach tourism is to use the Analytical Hierarchy Process (AHP). The results of the AHP analysis show that the priority strategies for developing Koneng Beach tourism are business tourism, community involvement tourism, and marine tourism